Comparative study of subclinical synovitis and periarticular bone changes in psoriasis patients: impact of biological therapy - Heba Elsayed Elshok; Abdelkawy A. Moghazy; Mostafa Farouk Balbaa; Amira M. Ibrahim (Egyptian Rheumatology and Rehabilitation, 2026)
Abstract Background Psoriasis (PsO) is increasingly recognized as a systemic inflammatory disease associated with subclinical musculoskeletal involvement that may precede psoriatic arthritis (PsA). This study aimed to evaluate the prevalence of subclinical synovitis and periarticular bone changes in PsO patients and to assess the impact of biological therapy compared to conventional treatment modalities. Patients and methods This case–control study included 50 PsO patients without clinical evidence of PsA and 25 age-, sex-, and BMI-matched healthy controls. Patients were divided into two groups: those receiving conventional therapy (group I) and those receiving biological therapy (group II). All participants underwent clinical evaluation, laboratory assessment, musculoskeletal ultrasound (MSUS) examination, and high-resolution computed tomography (HRCT) of the dominant hand. Results Group II patients had a significantly longer disease duration, averaging 10.01 ± 8.48 years, compared to 5.65 ± 6.48 years in group I ( p = 0.04). HRCT-detected erosions were present in 44% of group I, 28% of group II, and 4% of controls ( p = 0.01), while enthesophytes were detected in 76%, 44%, and 8%, respectively ( p < 0.001). Multiple enthesophytes were more frequent in group I (44%) compared to group II (16%) and controls (0%) ( p < 0.001). PASI score showed positive correlations with US scores including grey scale synovitis ( r = 0.59), global US inflammatory subscore ( r = 0.58), and total US score ( r = 0.57) (all p < 0.001), as well as HRCT enthesophyte number ( r = 0.38, p = 0.01) and height ( r = 0.39, p = 0.01). Total US score independently predicted HRCT-detected erosions and enthesophytes ( p < 0.05). Conclusion Subclinical musculoskeletal involvement is frequently observed in PsO patients without clinical arthritis. HRCT is sensitive for detecting early structural damage. Biological therapy was associated with a lower burden of subclinical structural bone changes, indicating a potential role in mitigating bone remodeling in the subclinical phase.